Response surface methodological approach for the prediction of tangential cutting forces in end milling of stainless steel - Patwari, Muhammed Anayet Ullah; Amin, A. K. M. Nurul; Faris, Waleed Fekry (2008)
The present paper discusses a response surface methodological approach for the prediction of tangential cutting force produced in end-milling operation of Stainless steel (SS304). It is difficult to predict accurately the cutting forces encountered in end milling operations due to large number of independent variables involved. In this work, an approach was undertaken to develop mathematical model based on RSM design for predicting the average tangential cutting force in end milling of SS304 in terms of cutting parameters cutting speed, feed rate, and axial depth of cut. All the individual cutting parameters affect on cutting force as well as their interaction are also investigated in this study. The experimental results indicate that the proposed mathematical models suggested could adequately describe the performance indicators within the limits of the factors that are being investigated. The adequacy of the predictive model was verified using ANOVA at 95% confidence level. This paper presents an approach to predict cutting force model in end milling of stainless steel using coated TiN insert under dry conditions and full immersion cutting.